Effect of Chest Physiotherapy on Respiratory Effectiveness in Children with Pneumonia - Lubis, Lisnawati; Siregar, Patimah Sari; Basri, Basri; Sucahyo, Dedek; Nurhayati, Evalatifah (Jurnal Kesmas Prima Indonesia, 2025)
Pneumonia remains a leading cause of morbidity and mortality in children, especially those with weakened immunity due to factors such as insufficient breast milk, malnutrition, HIV or measles infection, premature birth, or incomplete immunizations. Environmental exposures—including dust, cigarette smoke, and air pollution further elevate the risk. This study aimed to systematically review literature (2019–2024) on the effectiveness of chest physiotherapy in improving clinical outcomes, specifically respiratory rate, oxygen saturation, length of hospital stay, and symptomatic recovery in children with pneumonia. We conducted electronic searches on Google Scholar, NCBI, and accredited Indonesian journals using the keywords “chest physiotherapy” and “pneumonia in children.” From approximately 60 initially identified articles, eight met our inclusion criteria and were reviewed in full. Most studies were quasi‑experimental; one was a randomized controlled trial. Study populations ranged from infants (0–5 years) to older children (6–12 years). Interventions comprised postural drainage, clapping, vibration, percussion, deep‑breathing exercises, and effective coughing techniques. Results from eight studies indicated modest improvements in oxygen saturation and reductions in respiratory rate in some small trials. However, findings were inconsistent, with substantial heterogeneity in methodology, intervention protocols, and outcome reporting. Overall evidence quality was low to moderate. Chest physiotherapy may offer potential benefits in terms of oxygenation and respiratory rate in pediatric pneumonia patients. Nevertheless, current evidence remains limited and heterogeneous. High‑quality randomized controlled trials using standardized protocols are needed to establish stronger recommendations